Rainwater Harvesting: Quantity, Quality, Economics and State Regulations_Book - Ataur Rahman (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Rainwater harvesting (RWH) is the most popular alternative water source in many urban, peri-urban, and rural areas. Although rainwater is fresh in nature, it gets polluted from atmospheric contaminants, roof catchments, and the RWH system itself. The research questions which are the most relevant to RWH system include the optimum rainwater tank size for a given location and set of users, water quality from a RWH system, financial viability of a RWH system, and state regulations on the use of water from a RWH system. You are invited to submit a technical paper to this Special Issue of Water on these aspects of a RWH system.